Efektivitas Sosialisasi dan Edukasi Aman Bencana (BPDB) Jawa Barat - Mulyadi, Mulyadi; Rosadi, Barkah; Rumiasari, Mia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2023)
This research seeks to delineate the process of disseminating information and educating individuals by the West Java Regional Disaster Management Agency (BPBD) regarding disaster management and assess the effectiveness of these efforts. This is a qualitative study that employs a descriptive approach. The data were collected through observations, interviews, and documentary research. By applying Nakamura's theory, which comprises five key indicators encompassing goal attainment, efficiency, satisfaction of the target audience, responsiveness to customers, and system maintenance, we can draw conclusions about the training. The research findings lead to the conclusion that the socialization and education efforts related to disaster management by the West Java Regional Disaster Management Agency (BPBD) have been executed in accordance with their established plans and objectives. Furthermore, the influence of these socialization and education endeavors conducted by the West Java Regional Disaster Management Agency (BPBD) in the realm of disaster management can be deemed highly effective.